Prinsip-Prinsip Dakwah Antarbudaya - Ali, H. Baharuddin (Jurnal Berita Sosial, 2013)
Islam is a proselytizing religion. Islam developed in the midst of the people throughout the world through preaching. The success of Islamic propagation in inviting people to the right path, partly because Islam does not discriminate against race, nation, ethnicity and culture. Islamic preaching in the face of diverse human cultures, not just in the form of an invitation, but has a principle which is a basic guideline that refers to the obligation, the human response to God’s call, there is no element of coercion, it is rational and ethics enforcement in assessing good and bad things according to religious teachings (Islam).